In situ hybridization of the feline major satellite DNA FA-SAT in feline fibrosarcoma cell lines and feline fibrosarcoma tissue sections - Alfaro Alarcón, Alejandro; Justus Liebig University Giessen (My University, 2009)
Feline fibrosarcomas are the most common skin tumors of cats. Despite this high frequency and the publication of different hypotheses for their pathogenesis by several authors, the alterations accompanying the development of this tumor are still not completely understood.We studied the feline major satellite DNA (FA-SAT) hybridization pattern by FISH in four fibrosarcoma cell lines and one normal embryonic fibroblastic cell line as well as in 30 fibrosarcomas from 28 cats. Of the latter, tumor tissue biopsies and biopsies of non-affected skin of the same patient were analyzed.The hybridization pattern of the FA-SAT in the normal fibroblastic cell line differed significantly from that observed in all fibrosarcoma cell lines. The same observation was made for tumor tissues and fibroblasts from non-affected skin in paraffin-embedded material. These differences observed in vitro and in vivo suggest that alterations of the FA-SAT may be associated with chromosomal instability in the feline fibrosarcoma.Additionally, our FISH results show the usability of the designed method in differentiating tumor cells from normal skin fibroblasts in feline fibrosarcoma.

Feline Fibrosarkome sind die am häufigsten vorkommenden Hautumoren der Katze. Zwar gibt es verschiedene Hypothesen zur Pathogenese dieser Tumoren, letztendlich ist ihre Entwicklung aber noch in vielerlei Hinsicht nicht geklärt.Diese Studie untersuchte die feline major satellite DNA (FA-SAT) mittels FISH in Fibrosarkomzelllinien, in einer normalen embryonalen Fibroblastenzelllinie und 30 Fibrosarkomen von 28 Katzen. Von letzteren wurden Biopsien aus dem Tumorgewebe und aus nicht betroffenen gesunden Hautbereichen gewonnen.Es konnten signifikante Unterschiede im FA-SAT-Hybridisationsmuster zwischen der Fibroblastenzelllinie und den Fibrosarkomzelllinien belegt werden. Ebenso lagen Signalunterschiede zwischen Fibroblasten aus Tumorgewebe und Fibroblasten aus nicht betroffenen Hautarealen im Paraffin-eingebetteten Material vor.Diese in vitro und ex vivo ermittelten Unterschiede weisen auf eine mögliche Rolle der FA-SAT hinsichtlich chromosomaler Instabilität im felinen Fibrosarkom hin. Weiterhin konnte diese Arbeit den Nutzen der FISH von FA-SAT in der Differenzierung zwischen Tumorzellen und normalen Zellen in felinen Fibrosarkomen aufzeigen.
Untersuchung der feline major satellite DNA FA-SAT mittels In situ Hybridisierung in felinen Fibrosarkomzelllinien und in Fibrosarkomgewebe
Keywords: Fibrosarkom; major satellite DNA; Fibrosarcoma; major satellite DNA; ddc:610